Owner type, pyramidal structure and R&D Investment in China’s family firms - Luo, Jin-hui (Springer Nature, 2020)
Drawing on socioemotional wealth perspective and agency theory, this paper holds that lone-founder firms tend to engage more actively in R&D projects than do familycontrolled firms involving multiple family members as owners, while family ownership structure moderates that effect. Using a large sample of 5808 firm-year observations in China, the study found that lone-founder firms do more R&D than family-controlled firms, though the positive effect is less pronounced when founder’ ownership is higher and more pronounced when the divergence between founders’ ownership and control (resulted from pyramidal structures) is higher. These findings indicate that properties of family ownership structure, and particularly pyramidal ownership structure, are important contingencies of family firms’ R&D decisions. This yields implications for family business and researchers, as well as policymakers seeking to encourage innovativeness in the large family business sector.